Transparansi dan Akuntabilitas dalam Pengelolaan Dana Desa terhadap Pemberdayaan Masyarakat pada Desa Rumah Sumbul Kabupaten Deliserdang - Purba, Kartika; Gani, Abdul; Nazah, Khairatun (Lembaga Dongan Dosen, 2024)
The Indonesian government supports village activities and progress through village funds. But corruption in village funds occurs everywhere. The village is not getting more advanced and developing, the opposite is happening. The research aims to determine transparency and accountability in Village Fund Management towards Community Empowerment in Rumah Sumbul Village, Deliserdang Regency. The research is quantitative research. The research sample was 100 respondents. The sampling method is the Purposive Sampling method. Research data was collected through questionnaires. Processed and analyzed using multiple linear regression analysis with SPSS. The research results show that transparency and accountability in managing village funds have a positive and significant impact on community empowerment in Rumah Sumbul Village, Deliserdang Regency.